Species Composition of Tropical Understory Birds in Threatened East African Coastal Forests Based on Capture Data - Modest, Robert B.; Hassan, Shombe N. (International Journal of Zoology, 2016)
The East African coastal forests are subject of haphazard modification following anthropogenic pressures including tree cutting and clearing for agriculture. These activities, which are leading cause of habitat disturbance and species loss, are the major challenge in the management of sensitive wildlife species such as forest understory birds. This study investigated species composition of understory birds in the coastal forests of northeastern Tanzania to generate information for the management of the landscape and biodiversity in the area. Using mist nets, birds were trapped from core and edge habitats of representative forest patches. Trapped birds were classified to species level and categorized into bird guilds based on their levels of forest dependence. It was found out that species richness was influenced by forest patch size rather than level of habitat disturbance. Edge habitat was also found to be important in hosting higher number of forest understory birds, especially generalists—but this should be treated with caution because following habitat destruction that is ongoing in the study area, there is a danger of generalist wiping out specialist species due to competitive exclusion. Strict control measures to stop illegal tree cutting and agricultural activities near the forests were recommended for sustainable conservation of the understory birds in the forests.